Do shocks affect men’s and women’s assets differently? Evidence from Bangladesh and Uganda - Quisumbing, Agnes R.; Kumar, Neha; Behrman, Julia A. (International Food Policy Research Institute, 2014)
Bangladesh and Uganda were chosen, first, based on the availability of data from both countries before and after the 2007/08 food-price crisis (allowing the establishment of precrisis baseline values) and, second, because the two countries exhibit very different sociocultural traditions, implying that the gendered impacts of shocks in each country would be different.